(х+1)/(х-2) - х/(х+2) = 12/(х^2-4)
(х+1)/(х-2) - х/(х+2) = 12/(х^2-2^2)
(х+1)/(х-2) - х/(х+2) = 12/(х-2)(х+2) | (х-2)(х+2) (находим общий знаменатель.)
(х+1)(х+2) - х(х-2) = 12
х^2+2х+х+2-х^2+2х = 12
5х=12-2
5х=10
х=2

Ответы и объяснения

2013-10-16T16:16:39+04:00
Х+1/х-2-х/х+2-12/(х-2)(х+2)=0 умножаем на (х-2) (х+2), х не равно 2 и х не равно -2
(х+1) (Х+2) - х(х-2) - 12 = 0
х^+2x+x+2-x^2+2x-12=0
5x-10=0
x=2
(х+1)/(х-2) - х/(х+2) = 12/(х^2-4)
(х+1)/(х-2) - х/(х+2) = 12/(х^2-2^2)
(х+1)/(х-2) - х/(х+2) = 12/(х-2)(х+2) | (х-2)(х+2) (находим общий знаменатель.)
(х+1)(х+2) - х(х-2) = 12
х^2+2х+х+2-х^2+2х = 12
5х=12-2
5х=10
х=2